Effect of Cryopreservation on the Sperm DNA Fragmentation Dynamics of the Bottlenose Dolphin (Tursiops truncatus). Issue 2 (21st January 2015) - Sánchez‐Calabuig, MJ; López‐Fernández, C; Johnston, SD; Blyde, D; Cooper, J; Harrison, K; de la Fuente, J; Gosálvez, J
Contents Sperm DNA fragmentation is one of the major causes of infertility; the sperm chromatin dispersion test (SCDt) evaluates this parameter and offers the advantage of species‐specific validated protocol and ease of use under field conditions. The main purpose of this study was to evaluate sperm DNA fragmentation dynamics in both fresh and post‐thaw bottlenose dolphin sperm using the SCDt following different cryopreservation protocols to gain new information about the post‐thaw differential sperm DNA longevity in this species. Fresh and cryopreserved semen samples from five bottlenose dolphins were examined for sperm DNA fragmentation dynamics using the SCDt (Halomax®). Sperm DNA fragmentation was assessed immediately at collection and following cryopreservation (T0) and then after 0.5, 1, 4, 8, 24, 48 and 72 h incubation at 37°C. Serially collected ejaculates from four dolphins were frozen using different cryopreservation protocols in a TES‐TRIS‐fructose buffer (TTF), an egg‐yolk‐free vegetable lipid LP1 buffer (LP1) and human sperm preservation medium (HSPM). Fresh ejaculated spermatozoa initially showed low levels of DNA fragmentation for up to 48 h. Lower Sperm DNA fragmentation (SDF) was found in the second fresh ejaculate compared to the first when more than one sample was collected on the same day (p < 0.05); this difference was not apparent in any other seminal characteristic. While there was no difference observed in SDF between fresh and frozen–thawed sperm using the different cryopreservation protocols immediately after thawing (T0), frozen–thawed spermatozoa incubated at 37°C showed an increase in the rate of SDF after 24 h. Sperm frozen in the LP1℗ buffer had higher levels (p < 0.05) of DNA fragmentation after 24‐ and 48‐h incubation than those frozen in TTF or HSPM. No correlation was found between any seminal characteristic and DNA fragmentation in either fresh and/or frozen–thawed samples.